Circulating Irisin Levels in Patients with Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Jie Hu; Yani Ke; Fangping Wu; Shan Liu; Conghua Ji; Xiaohong Zhu; Ying Zhang (Gastroenterology Research and Practice)
Background and Aims. Previous studies have revealed the close relation of irisin with the occurrence and development of nonalcoholic fatty liver disease (NAFLD). A systematic review and meta-analysis were conducted to evaluate the association of circulating irisin levels and NAFLD. Methods. A systematic literature search of PubMed, Embase, Cochrane Library, Clinicaltrials.gov, WANFANG, CNKI, and CBM databases was performed for relevant articles till August 2020. The weighted mean difference (WMD) values and 95% confidence intervals (CIs) were estimated to compare the case-control studies and pooled results using meta-analysis. Results. The meta-analysis included 5 case-control studies with a total of 1087 people. The results revealed that the circulating irisin levels showed no significant difference between NAFLD and healthy groups (WMD=7.51 (-12.53, 27.56) ng/ml, P>0.05). Subgroup analysis based on races showed that the average irisin levels were higher in the NAFLD group than in the healthy group (WMD=13.53 (0.71, 26.34) ng/ml, P<0.05) in 4 Asian studies. Subgroup analysis based on disease severity from 3 Asian studies revealed that the average irisin levels were higher in the NAFLD group than in the healthy group (WMD=25.1 (22.85, 27.51) ng/ml, P<0.05 and WMD=13.52 (22.85, 27.51) ng/ml, P<0.05, respectively). Subgroup analysis including 3 studies from Asia suggested that the irisin levels were higher in mild NAFLD than in moderate-severe NAFLD (WMD=11.68 (9.03, 14.32) ng/ml, P<0.05). Conclusion. The average irisin levels might be higher in the NAFLD group than in the healthy group in Asians. The irisin levels in the mild NAFLD group might be higher than those in the moderate-severe group in Asians. It is important to monitor the changing trend of irisin levels in predicting the course of NAFLD disease and its changes.